Pengruh variasi Bentuk Paving Block terhadap Kuat Tekan - Arie Putra; Alex Kurniawandy; Azhari Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The purpose of this research is to know the effect of paving block original shape variations and test shape of paving block with SNI standard 03-0691-1996 against compressive strength. Mix design of paving block in this research used proctor methods with cement ratio and fine aggregate allowed 1 : 2,857. Beam specimen with dimension 20×10×8 cm and cube with dimension 8×8×8 cm and hexagon specimens with lateral side dimension 10 cm and heavy 8 cm and then cube with dimension 8×8×8 cm for testing of compressive strength, while the specimen of beam with dimension 20×10×8 cm and specimen of hexagon with lateral dimension 10 cm and heavy 8 cm for testing of water absorption with total specimen 46 sample. The testing of compressive strength and water absorption conducted at 28 days. The result of compressive strength value was produced by testing of compressive strength with compression machine and the test of ultrasonic pulse velocity (UPV) towards specimen of original shape and specimen of cube shape with SNI standard. The result of the research showed that testing result of compression strength with compression machine between original shape of paving block and cube shape with SNI standard there were significant differences. Compressive strength of specimen beam with dimension 20×10×8 cm with cube with dimension 8×8×8 cm and specimen of hexagon with lateral dimension 10 cm and heavy 8 cm and cube with dimension 8×8×8 cm were obtained for each of it 39,58 MPa ; 34,22 MPa ; 53,50 MPa dan 32,89 MPa. The Average of water absorption that was obtained for the beam specimen and hexagon were respectively 2,66 dan 2,62%. Keywords: paving block, original shape, cube shape, compressive strength, UPV, compression machine, water absorption and proctor method.